Current Trends in Combating Goods Smuggling - Overchenko , Yurii; Tyshchuk , Viktor (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article comprehensively analyzes commodity smuggling, one of the most pressing threats to economic security, financial stability, and international trade relations. The illegal movement of goods across state borders, which is exacerbated by globalization and the simplification of customs procedures, undermines tax revenues, promotes the expansion of the shadow economy, and funds organized crime. The study examines the results of recent scientific works, particularly those by O. O. Durov, R. O. Movchan, and G. Basu, which address the legal, organizational, and technological aspects of combating smuggling. The authors conduct a comparative analysis of international experience, highlighting the specifics of applying criminal and administrative sanctions in various countries.Attention is given to the analysis of the Ukrainian context, where smuggling is defined as the movement of goods across the customs border without proper control or with the concealment of this fact. This issue has become particularly acute in light of armed aggression and the growth of e-commerce. Implementing the latest technologies, including risk management systems, blockchain technologies, and big data analytics, is noted, which significantly enhances the effectiveness of customs control. An example is the computerized transit system NCTS, which facilitates the prompt exchange of customs information and reduces the risks associated with the illegal movement of goods.The article also emphasizes the need to integrate legislative changes, strengthen strict sanctions, and improve interagency coordination to create a comprehensive strategy to combat smuggling. It highlights the problems of misinformation and the lack of resources within law enforcement agencies, which complicate the detection and neutralization of illegal schemes. Recommendations are proposed for improving methods of identifying criminal networks, training specialists, and implementing innovative technologies as key factors in ensuring effective countermeasures against commodity smuggling in the context of national security.